2014
DOI: 10.1074/jbc.m113.536144
|View full text |Cite
|
Sign up to set email alerts
|

Normal Activation of Discoidin Domain Receptor 1 Mutants with Disulfide Cross-links, Insertions, or Deletions in the Extracellular Juxtamembrane Region

Abstract: Background: DDR1 is a constitutively dimeric receptor tyrosine kinase that is activated by collagen. The mechanism of transmembrane signaling is unknown.Results: DDR1 activation is unaffected by disulfide cross-links, insertions, or deletions in the extracellular juxtamembrane region.Conclusion: The extracellular juxtamembrane region of DDR1 does not transmit a conformational change across the cell membrane.Significance: The activation mechanism of DDR1 appears to be unique among receptor tyrosine kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…However, how collagen binding to the extracellular DS domains induces intracellular kinase activation is not known. In contrast to most other RTKs, which are thought to be present as monomers in the absence of ligand and to dimerise upon ligand binding [92], the DDRs are constitutive dimers [93][94][95]. Therefore, the model of ligand-induced receptor dimerisation does not apply to the DDRs.…”
Section: Ddr Signallingmentioning
confidence: 99%
“…However, how collagen binding to the extracellular DS domains induces intracellular kinase activation is not known. In contrast to most other RTKs, which are thought to be present as monomers in the absence of ligand and to dimerise upon ligand binding [92], the DDRs are constitutive dimers [93][94][95]. Therefore, the model of ligand-induced receptor dimerisation does not apply to the DDRs.…”
Section: Ddr Signallingmentioning
confidence: 99%
“…An alternative activation mechanism would be higher‐order receptor clustering , which does not preclude the presence of constitutive GPVI dimers in non‐activated platelets. Clustering has been demonstrated for many classes of receptor, including G‐protein‐coupled receptors , adhesion receptors such as platelet integrin α IIb β 3 , platelet C‐type lectin‐like receptor 2 , and, notably, discoidin domain receptor 1, a constitutively dimeric tyrosine kinase receptor for collagen .…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been suggested that stimulating DDR1 with its ligand, collagen, causes aggregation [32][33][34]. Here, we label DDR1 with a SNAP-tag that has been stochastically linked to Alexa488 or Alexa546.…”
Section: Resultsmentioning
confidence: 99%